CHARACTER EDUCATION VALUES IN THE ELEMENTARY SCHOOL ENGLISH TEXTBOOK ENTITLED “BASIC ENGLISH” FOR GRADE SIX - Windy Ayu Andini Rebowo Hadi; Mukminatus Zuhriyah (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2022)
One of the most important teaching materials is textbook. It is also inseparable from learning English in elementary school. Using English textbook in Elementary school to help a teacher in conveying material to their students. Textbooks that are suitable for use as teacher handbooks are those that are in accordance with the competency standards set by the ministry of education. The aims of the research are to analyze: the values of character education as reflected in the sixth grade English textbook of elementary school entitled "Basic English" which is used at SDN Jombatan 5 Jombang and how to implement character education values ??in the textbook. The method used in this study was a qualitative descriptive approach using interactive content analysis. The subjects of this study were 14 themes of subject matter in English textbook “Basic English”. The results of this study stated that the sixth grade English textbook entitled "Basic English" Religiousness, honesty, intelligence, toughness, democracy, care, independence, Logical thinking, critical, creative, and innovative, courage takes risk, action oriented, leadership, hard work, responsibility, healthy lifestyle, discipline, confidence, curiosity, loving science, Awareness of rights and self-and other obligations and Adherence to social rules and others characters education values are namely appreciating the work and achievements of others, politeness, nationalism, and respecting diversity. And those values are explained implicitly and explicitly.